2021
DOI: 10.4103/tjo.tjo_31_20
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravitreal ranibizumab and posterior subtenon triamcinolone acetonide injections for patients with diabetic macular edema refractory to intravitreal ranibizumab monotherapy

Abstract: PURPOSE: The purpose of this study is to compare the efficacy of intravitreal ranibizumab (IVR) alone and concurrent IVR with posterior subtenon triamcinolone acetonide (PSTA) injection for patients with diabetic macular edema (DME) refractory to IVR monotherapy. MATERIALS AND METHODS: We enrolled 43 eyes of 43 patients with DME who received at least three times of IVR, which resulted in poor anatomical responses, with central foveal thickness (CFT) reduction <10% and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…This systematic review and meta‐analysis investigated the efficacy and safety of combined intravitreal anti‐VEGF and steroid treatment for refractory DME. The majority of studies in our review found that combination therapy is significantly more effective for anatomical outcomes in the treatment of resistant DME compared with anti‐VEGF monotherapy (Ahmadieh et al, 2008; Chiu et al, 2021; Eriş et al, 2019; Limon, 2021; Maturi et al, 2015, 2018; Yolcu & Sobaci, 2015). Two studies (one RCT and one non‐randomized prospective) found that addition of intravitreal steroids promoted faster visual improvement, but not significantly better final visual outcomes compared with anti‐VEGF monotherapy (Ahmadieh et al, 2008; Limon, 2021).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This systematic review and meta‐analysis investigated the efficacy and safety of combined intravitreal anti‐VEGF and steroid treatment for refractory DME. The majority of studies in our review found that combination therapy is significantly more effective for anatomical outcomes in the treatment of resistant DME compared with anti‐VEGF monotherapy (Ahmadieh et al, 2008; Chiu et al, 2021; Eriş et al, 2019; Limon, 2021; Maturi et al, 2015, 2018; Yolcu & Sobaci, 2015). Two studies (one RCT and one non‐randomized prospective) found that addition of intravitreal steroids promoted faster visual improvement, but not significantly better final visual outcomes compared with anti‐VEGF monotherapy (Ahmadieh et al, 2008; Limon, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…Chiu et al conducted a retrospective study of 43 Taiwanese adults with persistent DME and poor anatomical response after at least three doses of IVR (Chiu et al, 2021). 20 eyes continued PRN injections of IVR and 23 eyes received combined IVR and PSTA with at least 1‐year follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations